Taliban narratives the use and power of stories in the Afghanistan conflict - Johnson, Thomas H.; DuPee, Matthew; Shaaker, Wali (Oxford University Press, 2017)
"Why has the Taliban been so much more effective in presenting messages that resonate with the Afghan population than the United States, the Afghan Government and their allies? This book, based on years of field research and the assessment of hundreds of original source materials, examines the information operations and related narratives of Afghan insurgents, especially the Afghan Taliban, and investigates how the Taliban has won the information war. Taliban messaging, wrapped in the narrative of jihad, is both to the point and in tune with the target audiences it wishes to influence. On the other hand, the United States and its Kabul allies committed a basic messaging blunder, failing to present narratives that spoke to or, often, were even understood by their target audiences. Thomas Johnson systematically explains why the United States lost this 'battle of the story' in Afghanistan, and argues that this defeat may have lost the U.S. the entire war, despite its conventional and technological superiority."--Cover flap.